Free Radical Scavenging Activity of Hydroalcoholic Extracts of Dried Flowers of Nymphaea Stellata Willd - SACHIN UTTAM RAKESH; PRIYANKA R. PATIL; V. R. SALUNKHE (International Journal of Pharma and Bio Sciences, 2010)
The free radical scavenging potential of the dried flower of plant Nymphaea stellata Willd was studied by using different in vitro antioxidant models of screening. The hydroalcoholic extract at 500 µg/ml showed maximum scavenging of the in vitro riboflavin NBT assay (26.22%), hydroxyl radical scavenging activity (26.06%), DPPH (25.70%) and nitric oxide radicals (25.11%). However, the extract showed only moderate scavenging activity of total antioxidant capacity (15.25%). DPPH- Radical scavenging activity, Scavenging of superoxide radical, Scavenging of nitric oxide radical, Iron chelating activity, Hydroxyl radical scavenging activity, Rapid screening for antioxidant activity, Total antioxidant capacity and Riboflavin NBT method were used as in- vitro antioxidant models for screening of antioxidant potential. The extract showed significant scavenging and IC50 value as compared to standard Ascorbic acid. Further investigation is necessary to find out such activities using other solvents for extraction.